The design of a system dynamics model of crowdfunding for support of new knowledge-based IT startups. (15th October 2020) - Saryazdi, Ali Haji Gholam; Ghatari, Ali Rajabzadeh; Mashayekhi, Alinaghi; Hassanzadeh, Alireza
Considering the problem of funding start-ups because of their nature, some entrepreneurs developed crowdfunding in which funding is done via social network. Crowdfunding is a complicated and dynamic phenomenon. In addition, studies conducted on crowdfunding are not significant in number and they have been conducted in exploratory and partial manner. As a result, it is necessary to adopt an approach capable of understanding complex dynamic phenomena so as to be able to explain a crowdfunding. The present paper designs a system dynamics model of crowdfunding for support of new Iranian knowledge-based IT startups so as to highlight the complexities and dynamics of crowdfunding. The results of model simulation suggest that the reward model will develop to a higher extent due to higher alignment with IT business designs. Also, the model suggests that passing of relevant regulations and monitoring of platforms improved the quality of IT business designs and secured the success of the companies after funding.